Dairy input agri-entrepreneurs’ practices and their effect on inputs market participation by smallholder farmers in Tanzania - Kundu, R.N.; Bett, H.K.; Rao, E.J.O. (Elsevier, 2024)
Dairy productivity per cow remains lower than the production ability amid increasing population. Among major reasons for this is the lower uptake of improved dairy inputs by smallholder dairy farmers. We characterized dairy input providers' business practices using Latent class analysis (LCA) and determined the effect of these business practices on the uptake of inputs by smallholder dairy farmers in Tanga and Kilimanjaro regions using OLS. From LCA, Bayesian Information Criteria (BIC) revealed a 3-class model as the most parsimonious and best fit (2153.071). The latent class (LC) membership of the input/service entrepreneurs for classes I, II, and III was 37.6% (35), 9.7% (9), and 52.7% (49), respectively. Using item response probabilities, we classified class I, II and III as ‘High business activities and business promotional practices’, ‘Low business activities, medium business promotional activities’, and ‘Medium business activities, Low business promotional activities’. Extension services provision was significant across all the classes with probability values greater than 0.5. The OLS model revealed that LC I and II were significant at 1% while LC III was significant at 5%. Education level and Moshi Rural District were negatively significant. Technical training of input entrepreneurs and capacity building on bundling relevant information alongside inputs is necessary for knowledge sharing with farmers. Networking, collaborations, and alliances among input/service entrepreneurs and between entrepreneurs and dairy farmers should be fostered for adequacy in technical information sharing and connecting farmers to other input suppliers. There is need for entrepreneurs to invest in rural areas and improve information and input access by the farmers. The study explored private dairy entrepreneurs as alternative extension services providers as a business strategy to enhance uptake of improved inputs by smallholder farmers. This study is relevant in making workable decisions towards implementing programmes geared towards increasing the improved input uptake in developing countries.